Introduction to a family of Thukral k-order method for finding multiple zeros of nonlinear equations (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
A new one-point k-order iterative method for finding zeros of nonlinear equations having unknown multiplicity is introduced.  In terms of computational cost the new iterative method requires k+1 evaluations of functions per iteration.  It is shown that the new iterative method has a convergence of order k.